The Reception of the Non-Human Living Beings in Philosophical and Practical Approaches - Kaluđerović, Željko (Epistēmēs Metron Logos, 2020)
In this paper, the author explores the reception of the non-human living beings in modern philosophical and practical approaches. The analysis is aimed at examining both the views of the representatives of classical anthropocentrism, as well as the theses of the representatives of various non-anthropocentric teachings. Anthropocentrism is, in short, a worldview that is based on Aristotle’s vision of man as a special being among other natural beings. Advocates of the questioning of the dominant anthropocentric perspective of the cosmos, on the other hand, are trying to establish the new relation by relativizing of the difference between humans and non-human living beings, by attributing specifically human qualities and categories, such as dignity, moral status and rights, as well as feelings, memories, communication, consciousness and thinking to non-human living beings. Non-anthropocentrists, consequently, believe that it is necessary to relax the usual strict hierarchy among beings in nature, that is, the discrediting of animals in relation to man, and that within the applied ethics, alias bioethics, it is possible, even necessary, to establish the "animal ethics".